Political Obligation: Its Scope and Limits in Islamic Political Doctine (American Journal of Islam and Society, 1986)
I. political Allegiance: Nature and ExtentThe need for and the importance of government in Islam has been thesubject of extensive research and debates since the early days of Islam. Naturally,there is a general consensus among Muslim jurists on the obligatory natureof installing a government or a kind of central authority to sakguad the veryexistence of the community. Although obedience to legitimate authority isqualified and conditional, the Shari'ah attaches great importance to fulfillmentof the Muslims' obligations trrward their legitimate government and considersit a religious obligation of the highest degree. As Muhammad Asadpointed out correctly, what is at stake here is the unity of the Community:So long as the state conforms in its principles and methods to thedemands of the Shari'ah, a Muslim citizen's duty of obedience tothe govenment is a religious obligation. In the words of the prophet,"He who withdraws his hand from obedience [to the amir] willhave nothing in his favor when he meets Allah on the Day of Resurrection;and he who dies without having considered himself boundby a pledge of allegiance [literally, 'While there is no pledge ofallegiance on his neck'] had died the death of the Time of Ignorance[i.e., as an unbeliever]."In accordance with the principle of Muslim unity so strongly emphasized in the Qur'an and Sunnah, any attempt to disrupt that unity must be regardedin the Quran and Sunnah, any attempt to disrupt that unity must be regarded as a crime of the highest order-in fact, as hightreason- and must be punished severely. Consequently, the Prophet commanded ...